2003
DOI: 10.1037/0022-3514.84.4.822
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of being present: Mindfulness and its role in psychological well-being.

Abstract: Mindfulness is an attribute of consciousness long believed to promote well-being. This research provides a theoretical and empirical examination of the role of mindfulness in psychological well-being. The development and psychometric properties of the dispositional Mindful Attention Awareness Scale (MAAS) are described. Correlational, quasi-experimental, and laboratory studies then show that the MAAS measures a unique quality of consciousness that is related to a variety of well-being constructs, that differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

421
10,123
35
539

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9,928 publications
(11,118 citation statements)
references
References 117 publications
421
10,123
35
539
Order By: Relevance
“…The original MAAS (Brown & Ryan, 2003) is a widely-used scale to assess an individual’s dispositional mindfulness. It has 15 items, each rated on a 6-point scale from 1 (always) to 6 (never).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original MAAS (Brown & Ryan, 2003) is a widely-used scale to assess an individual’s dispositional mindfulness. It has 15 items, each rated on a 6-point scale from 1 (always) to 6 (never).…”
Section: Methodsmentioning
confidence: 99%
“…Mindfulness refers to one’s general tendency to be able to attend to the present moment nonjudgmentally and purposefully (Brown & Ryan, 2003). As one’s state of mindfulness may be unstable and sensitive to change, dispositional mindfulness has been frequently assessed in the literature (Chiesa, Calati, & Serretti, 2011; Garland, Gaylord, & Fredrickson, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, this physiological dysregulation may serve as an indicator of a reduced capacity to monitor and therefore predict, one's environment. According to Brown and Ryan (2003), individuals naturally exhibit differences in the propensity to be engaged with, and responsive to, their surroundings; this personal disposition is referred to as mindfulness (Brown, Goodman, & Inzlicht, 2012), and it has been associated with increased sympathetic arousal (Lumma, Kok, & Singer, 2015), as well as greater self‐regulation (Short, Mazmanian, Oinonen, & Mushquash, 2016). Notably, Krzeczkowski, Robb, and Good (2017) found that individuals with a history of concussion who endorsed greater trait mindfulness presented with fewer postconcussive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Such acceptance or understanding of one's state appears to be important for those with chronic pain [75]. IY is also associated with mindful awareness, a concept that has been integrated in empirically-validated approaches including cognitive-behavioral therapy [76]. Mindfulness is an openness or receptive awareness to what is occurring in the present.…”
Section: Introductionmentioning
confidence: 99%